Study on small coal pillar in gob-side entry driving and control technology of the surrounding rock in a high-stress roadway - Wang, Wen; Wu, Yiheng; Lu, Xiaowei; Zhang, Guangjie (Frontiers in Earth Science, 2023)
In order to solve the problems of mine mining succession tension, serious roadway deformation and support difficulties, the gob-side entry driving technology is adopted in ZhaoGu No.1 mine. In order to ensure the stable support effect of along-air tunneling under high stress, the key parameters of coal column need to be studied. Based on the breakage characteristics of the basic top large structure of the key layer, combined with the theory of internal and external stress field and the theory of limit equilibrium zone, the location of the breakage line of the roof plate in the mining hollow area is determined, and the calculation formula of the vertical stress of the coal pillar is proposed. FLAC3D numerical simulation software was used to simulate the vertical stress characteristics of the coal pillar and the surrounding rock of the roadway under the technical plan of leaving 4.5m coal pillar around the geological conditions of the mine, and to verify the actual measurement on site. The results show that the basic top break is located at 2.65m on the side of the coal pillar in the near mining area, and there is a "trapezoidal" internal stability zone of the coal pillar, which can guarantee the lasting and stable support effect of the roadway; the displacement of the two helpers of the roadway is between 100-500mm, and the displacement of the top and bottom plate is less than 300mm, which ensures the roadway surrounding rock under the high stress condition. safety of the roadway under high stress conditions.